Estimating the scope for savings in referrals and drug prescription costs in the general Practice units of a UK primary care trust - Thanassoulis, Emmanuel (2013)
This paper explores the potential for cost savings in the general Practice units of a Primary Care Trust (PCT) in the UK. We have used Data Envelopment Analysis (DEA) to identify benchmark Practices, which offer the lowest aggregate referral and drugs costs controlling for the number, age, gender, and deprivation level of the patients registered with each Practice. For the remaining, non-benchmark Practices, estimates of the potential for savings on referral and drug costs were obtained. Such savings could be delivered through a combination of the following actions: (i) reducing the levels of referrals and prescriptions without affecting their mix (£15.74 m savings were identified, representing 6.4% of total expenditure); (ii) switching between inpatient and outpatient referrals and/or drug treatment to exploit differences in their unit costs (£10.61 m savings were identified, representing 4.3% of total expenditure); (iii) seeking a different profile of referral and drug unit costs (£11.81 m savings were identified, representing 4.8% of total expenditure).